Analytical assessment of asphalt odor patterns in hot mix asphalt production. (20th January 2018) - Autelitano, Federico; Giuliani, Felice
Abstract: During the various stages of asphalt paving mixtures production and placement, as a result of binder heating, a complex mixtures of hydrocarbons and volatile organic compounds (VOCs) is released into the atmosphere. As far as hot mix asphalt plants is concerned, several standards and directives were drawn up for limiting the emissions of certain specific substances, without setting any specific limit on the odorous perspective. But, odor is increasingly considered an atmospheric pollutant that can have a significant negative impact on both quality of life and economic activity. The odorous flows of HMA emitted in plants or during the paving operations and hot-in-place recycling processes in the worksites can severely limit the usability of the territory. Advances in sensor technology have made possible the development of artificial olfactory systems (AOS), which are devices designed to mimic the human olfactory system capable of characterizing osmogene mixtures. However, their potentialities have not been explored until now at any stages of asphalt and asphalt mixtures production chain. Thus, the main purpose of this study was an analytical-sensory characterization, mainly based on AOS approach, of asphalt emissions generated during the various stages of road pavement construction. The analytical and sensory analyses have firstly demonstrated the effective application of these instruments in the pavement engineering sector: an odor fingerprint of asphalt emissions, specific for each type of binder and temperature class, was determined. Thanks to the photoionization, a technique which allow the detection of organic compounds in gaseous mixtures, a pseudo-hyperbolic relationship between the release of airborne substances in asphalt emissions and the heating temperature was identified; whereas the AOS demonstrated that this increase of VOCs corresponded contextually to a change in their odorous patterns. Moreover, the existence of variations in the odor fingerprints of different asphalt binders heated at the same temperature was assessed. Through a specific statistical approach for the treatment and post-processing of data and the following elaboration of a geometric based procedure for the determination of the numerical inter-class separation, a quantitative value to the purely qualitative response of the AOS was assigned.